Comparison of Fractional Picosecond 1064-nm Laser and Fractional Carbon Dioxide Laser for Treating Atrophic Acne Scars: A Randomized Split-Face Trial - Punyaphat Sirithanabadeekul (2022)
BACKGROUND: To date, no studies have compared the fractional picosecond 1064-nm laser (FxPico) and fractional carbon dioxide laser (FxCO2) for the treatment of acne scars. OBJECTIVE: To compare the efficacy and safety between FxPico and FxCO2 for treating facial atrophic acne scars. MATERIALS AND METHODS: Twenty-five Asian patients with mild to moderate atrophic acne scars underwent single sessions of randomized split-face treatment with FxPico and FxCO2. Clinical efficacy was assessed by photographs, skin imaging analysis, and patient satisfaction. The adverse events were recorded on every visit. Skin biopsies were performed immediately and 3 months after treatment. RESULTS: The physician improvement scores for skin texture and atrophy significantly increased on the FxPico sides, but no significant difference was observed between FxPico and FxCO2. Skin imaging also showed significant improvement on both sides for scar volume. Postinflammatory hyperpigmentation (PIH) was not reported on FxPico sides, whereas 6 patients (24%) experienced mild PIH on FxCO2 sides. Immediate post-FxPico skin biopsy revealed laser-induced optical breakdown with photoacoustic columns. Collagen and elastic fibers increased at 3 months after both treatments. CONCLUSION: FxPico was as effective as FxCO2 in treating atrophic acne scars, correlating with evidence of tissue remodeling with more safety profiles.